HUBUNGAN ANTARA KEBIASAAN MEMBACA ASMAUL HUSNA DENGAN KECERDASAN EMOSIONAL SISWA KELAS XI MA NURUL UMMAH YOGYAKARTA - Lili Khoirunnisa (Department of Islamic Education, The State Islamic University Sunan Kalijaga Yogyakarta, 2017)
This research aims to describe emotional quotient and reading habit of asmaul husna of students and to examine relationship between of both. The subject of this research were all of students in grade XI MA (Senior High School) Nurul Ummah Yogyakarta as many as 34 people. Interviews, scale of emotional quotient, and reading habit asmaul husna questionnaire are used as an instrument in data collection. The results show: first, level of emotional quotient of students in grade XI MA Nurul Ummah Yogyakarta are in the high category. Second, level of reading habit asmaul husna of students in grade XI MA Nurul Ummah Yogyakarta are in the high category. Third, there’s positive and significant correlation (rxy=0,614, p=0,001) between reading habit of asmaul husna and emotional quotient of students in grade XI MA Nurul Ummah Yogyakarta. Fourth, the contribution of reading habit Asmaul Husna toward emotional quotient of students in grade XI MA Nurul Ummah Yogyakarta is 37,70%. Keywords: reading habit asmaul husna, emotional quotient, student grade XI